2008
DOI: 10.1111/j.1365-2222.2008.03006.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide evaluation in upper and lower respiratory tracts in nasal polyposis

Abstract: The medical treatment of NP improves both airway reactivity and obstruction, whatever the presence of asthma, suggesting a functional link between upper and lower airway functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 25 publications
1
31
0
3
Order By: Relevance
“…Actually, an inverse correlation between nasal NO levels and the extent of sinus disease and the number of occluded paranasal sinuses has been reported [71,75,76]. The hypothesis of occluded sinus ostia was supported by the fact that after medical [75,77] and surgical [75] treatment of nasal polyps, nasal NO levels were significantly elevated. Especially in surgically treated patients, nasal NO levels were more elevated than in subjects who underwent pharmacological therapy [19].…”
Section: No In Crs With Nasal Polypsmentioning
confidence: 60%
See 1 more Smart Citation
“…Actually, an inverse correlation between nasal NO levels and the extent of sinus disease and the number of occluded paranasal sinuses has been reported [71,75,76]. The hypothesis of occluded sinus ostia was supported by the fact that after medical [75,77] and surgical [75] treatment of nasal polyps, nasal NO levels were significantly elevated. Especially in surgically treated patients, nasal NO levels were more elevated than in subjects who underwent pharmacological therapy [19].…”
Section: No In Crs With Nasal Polypsmentioning
confidence: 60%
“…Nasal polyposis is considered to be a chronic inflammatory condition in the nasal and paranasal sinus cavities, with symptoms such as nasal obstruction, anterior and posterior rhinorrhea, sneezing, loss of smell and facial pain [77]. It usually occurs in association with CRS, but the precise etiology of nasal polyps still remains unclear.…”
Section: No In Crs With Nasal Polypsmentioning
confidence: 99%
“…Olfactory NO is thought to have three main functions: protection, mucociliary clearance, and airborne messengership. Interestingly, a study on the role of nasal NO in the inflammatory process found an improvement in nasal polyposis (Delclaux et al, 2008). Nasal NO has been proposed to be used as a diagnostic tool and also for treatment of various respiratory diseases.…”
Section: Olfactionmentioning
confidence: 99%
“…Zuverl ä ssige Normwerte k ö nnen aufgrund der gro ß en interindividuellen Schwankungen nicht angegeben werden [173] . Mittels der Messung des nasalen NO kann man nicht-invasiv Patienten mit einer chronischen Rhinosinusitis mit Polypenbildung von solchen ohne Polypen und Gesunden unterscheiden [174] und positive, medikament ö se Behandlungseff ekte best ä -tigen [175] . Gr ö ß te Unterschiede zu einer Normalpopulation lie ß en sich bei Patienten mit prim ä rer zili ä rer Dyskinesie und zystischer Fibrose nachweisen [176] , sodass f ü r diese Erkrankungen nasales NO als nicht-invasives Screeninginstrument diskutiert wird [177] .…”
Section: Messung Des Exspiratorischen Nasalen Stickstoff -Monoxids (No)unclassified